Azithromycin and high-dose vitamin D for treatment and prevention of asthma-like episodes in hospitalised preschool children: study protocol for a combined double-blind randomised controlled trial. Issue 4 (13th April 2022) - Kyvsgaard, Julie Nyholm; Ralfkiaer, Ulrik; Følsgaard, Nilofar; Jensen, Trine Mølbæk; Hesselberg, Laura Marie; Schoos, Ann-Marie M; Bønnelykke, Klaus; Bisgaard, Hans; Stokholm, Jakob; Chawes, Bo
Abstract : Introduction: Previous randomised controlled trials (RCTs) suggest antibiotics for treating episodes of asthma-like symptoms in preschool children. Further, high-dose vitamin D supplementation has been shown to reduce the rate of asthma exacerbations among adults with asthma, while RCTs in preschool children are lacking. The aims of this combined RCT are to evaluate treatment effect of azithromycin on episode duration and the preventive effect of high-dose vitamin D supplementation on subsequent episodes of asthma-like symptoms among hospitalised preschoolers. Methods and analysis: Eligible participants, 1–5 years old children with a history of recurrent asthma-like symptoms hospitalised due to an acute episode, will be randomly allocated 1:1 to azithromycin (10 mg/kg/day) or placebo for 3 days (n=250). Further, independent of the azithromycin intervention participants will be randomly allocated 1:1 to high-dose vitamin D (2000 IU/day+ standard dose 400 IU/day) or standard dose (400 IU/day) for 1 year (n=320). Participants are monitored with electronic diaries for asthma-like symptoms, asthma medication, adverse events and sick-leave. The primary outcome for the azithromycin intervention is duration of asthma-like symptoms after treatment. Secondary outcomes include duration of hospitalisation and antiasthmatic treatment. The primary outcome for the vitamin D intervention is the number of exacerbations during the treatment period. Secondary outcomes include time to first exacerbation, symptom burden, asthma medication and safety. Ethics and dissemination: The RCTs are approved by the Danish local ethical committee and conducted in accordance with the guiding principles of the Declaration of Helsinki. The Danish Medicines Agency has approved the azithromycin RCT, which is monitored by the local Unit for Good Clinical Practice. The vitamin D RCT has been reviewed and is not considered a medical intervention. Results will be published in peer-reviewed journals and presented at international conferences. Trial registration numbers: NCT05028153, NCT05043116 .